How do Astrophysics and the Qur'an Perceive the Extraterrestrial Life? A Qualitative Study - Rahma, Siti Nur; Suliyanah, Suliyanah; Halim, Abdul (Jurnal Pendidikan Fisika, 2022)
The topic of extraterrestrial life is still only a theory and the truth is still being investigated. Therefore, this research aims to analyze the beginning formation of the universe according to astrophysics and the Qur’an, astrophysics discoveries about extraterrestrial life, and letters in the Qur’an that hint at extraterrestrial life, as well as analyzing the relationship between astrophysics and letters in the Qur’an related to extraterrestrial life. This research is qualitative research with a method consisting of library research and interviews. The primary data of this research comes from scientific articles of previous research, relevant books, and interpretations of Qur’an verses. The secondary data were obtained through the results of interviews with experts. The data analysis technique in this study was adapted from the analysis technique of Miles & Huberman, while the verses of the Qur’an used the Kemenag interpretation with a scientific interpretation style. The results show that in line with the astrophysical discoveries, the creation of the universe and the existence of extraterrestrial life are also hinted at in the Qur'an. In addition, the alleged presence of water on other planets also supports the signs in the Qur'an. Based on the results, it can be concluded that there is no dichotomy between astrophysical discoveries and signs in the Qur'an regarding extraterrestrial life.